Antifungal activity and patterns of N-acetyl-chitooligosaccharide degradation via chitinase produced from Serratia marcescens PRNK-1. (December 2017) - Moon, Chaeyeong; Seo, Dong-Jun; Song, Yong-Su; Hong, Sin-Hyoung; Choi, Seung-Hee; Jung, Woo-Jin
Abstract: Serratia marcescens PRNK-1, which has strong chitinolytic activity, was isolated from cockroaches ( Periplaneta americana L.). The chitinase from S. marcescens PRNK-1 was characterized after incubation in a 0.5% colloidal chitin medium at 30 °C for 3 days. The molecular weights of three bands after staining for chitinase activity were approximately 34, 41, and 48 kDa on an SDS-PAGE gel. S. marcescens PRNK-1 strain strongly inhibited hyphal growth of Rhizoctonia solani and Fusarium oxysporum. Thin-layer chromatography (TLC) and high performance liquid chromatograph (HPLC) analyses were conducted to investigate the degradation patterns of N -acetyl-chitooligosaccharides by PRNK-1 chitinase. The N -acetyl-chitooligosaccharides: N -acetyl-chitin dimer (GlcNAc)2, N -acetyl-chitin trimer (GlcNAc)3, and N -acetyl-chitin tetramer (GlcNAc)4 were degraded to (GlcNAc)1-3 on a TLC plate. In an additional experiment, (GlcNAc)6 was degraded to (GlcNAc)1-4 on a TLC plate. The optimal temperature for chitinase activity of the PRNK-1 was 50 °C, producing 32.8 units/mL. As seen via TLC, the highest degradation of (GlcNAc)4 by PRNK-1 chitinase occurred with 50 °C incubation. The optimal pH for chitinase activity of PRNK-1 was pH 5.5, producing 24.6 units/mL. As seen via TLC, the highest degradation of (GlcNAc)4 by PRNK-1 chitinase occurred at pH 5.0–6.0. These results indicate that chitinase produced from S. marcescens PRNK-1 strain showed strong antifungal activity and potential of production of N -acetyl-chitooligosaccharides. Highlights: S. marcescens PRNK-1, which has strong chitinolytic activity, was isolated from Cockroaches. Bands for chitinase activity were approximately 34, 41, and 48 kDa on an SDS-PAGE gel. S. marcescens PRNK-1 strongly inhibited hyphal growth of R. solani and F. oxysporum. The highest degradation of (GlcNAc)4 by PRNK-1 chitinase occurred with 50 °C incubation. The highest degradation of (GlcNAc)4 by PRNK-1 chitinase occurred at pH 5.0–6.0.